Techno-economic and environmental analyses of a grid-connected renewable energy power system in Madura, Indonesia. Issue 1 (31st December 2023) - Amir, Nizar; Gozan, Misri; Lee, Moonyong; Winarso, Kukuh
Abstract : Madura Island, Indonesia, which is dominated by lowlands, is closer to the equator and has a warmer and drier climate than its nearest neighbour, Java Island. Despite its aridity, agriculture is among the primary economic activities of its inhabitants. Hence, renewable solar and biomass energy are available to be harvested. The techno-economic and environmental aspects of a grid-connected power system were analyzed using solar and biomass energy source data from two rural areas of Madura. Several configurations were simulated and optimised using HOMER software. A solar – biomass hybrid system was predicted to provide cost-effective power generation. Analysis of economic indicators (e.g. net present cost and cost of energy) suggested that these projects are financially feasible. Greenhouse gas emission predictions were more than 56% lower for the grid-connected solar-biomass hybrid system than grid-only supply. Solar – biomass hybrid systems can therefore serve as cost-effective modes of power generation for rural areas in Madura and are recommended.